2008
DOI: 10.1097/ta.0b013e31815eb12a
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intravenous Ethanol Versus Diazepam for Alcohol Withdrawal Prophylaxis in the Trauma ICU: Results of a Randomized Trial

Abstract: Concerning the prophylaxis of AWS, intravenous ethanol offers no advantage over diazepam with respect to efficacy or adverse sedative effects. The purported benefit of intravenous ethanol as a prophylactic agent against AWS was not evident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 13 publications
0
37
0
4
Order By: Relevance
“…102,111 Severe alcohol withdrawal syndrome that is refractory to high-dose benzodiazepines has been treated successfully with the addition of phenobarbital or propofol. 104,112 Weinberg et al 113 have shown the use of IV alcohol infusion to be as equally effective as diazepam in the prevention of In our experience, patients with AUDs may develop signs of physical and possibly "autonomic agitation" with inadequate sedation. 89 Patients may develop fever, tachycardia, and hypertension when sedation is inadequate, although evidence for these occurring in broad cohorts of patients with AUDs are lacking because diagnosis of alcohol withdrawal syndrome rests on patients self-reporting symptoms of irritability, nausea, and headache.…”
Section: Management Of Sedationmentioning
confidence: 96%
“…102,111 Severe alcohol withdrawal syndrome that is refractory to high-dose benzodiazepines has been treated successfully with the addition of phenobarbital or propofol. 104,112 Weinberg et al 113 have shown the use of IV alcohol infusion to be as equally effective as diazepam in the prevention of In our experience, patients with AUDs may develop signs of physical and possibly "autonomic agitation" with inadequate sedation. 89 Patients may develop fever, tachycardia, and hypertension when sedation is inadequate, although evidence for these occurring in broad cohorts of patients with AUDs are lacking because diagnosis of alcohol withdrawal syndrome rests on patients self-reporting symptoms of irritability, nausea, and headache.…”
Section: Management Of Sedationmentioning
confidence: 96%
“…However, the many disadvantages of ethanol use for this purpose-the need to monitor blood levels, the unpredictable elimination kinetics, and many other possible adverse effects-make it difficult to use this treatment safely and reliably [54][55][56]. A few recent studies have compared ethanol to other commonly used medications and demonstrated no advantage of ethanol with respect to efficacy or adverse sedative effects [57][58][59].…”
Section: Goals Of Aws Treatmentmentioning
confidence: 97%
“…46 Although some suggest the use of ethanol itself to prevent alcohol withdrawal syndromes, an RCT conducted in trauma patients admitted to the SICU with a history of significant daily alcohol intake compared a strategy of intravenous ethanol with one of scheduled benzodiazapines and found no difference in efficacy or adverse outcomes. 109 More recently Ungur et al 110 published a systematic review of RCTs assessing prevention and therapy for alcohol withdrawal syndromes in trauma, surgical, and medical ICUs. The authors conclude that benzodiazepines are effective and safe for the prevention of alcohol withdrawal syndromes as well as for their treatment.…”
Section: Deliriummentioning
confidence: 98%